Mycobacterium bovis mutant in the virulence factors PhoP, ESAT-6 and CFP-10 persisted in mouse organs after a year post-vaccination - Blanco, Federico Carlos; Vazquez, Cristina Lourdes; Garcia, Elizabeth Andrea; Rocha, Rosana Valeria; Klepp, Laura Ines; Bigi, Fabiana (Elsevier, 2024)
A vaccine for bovine tuberculosis is urgently needed. The BCG vaccine (the Bacille Calmette-Guérin), currently the only licensed vaccine for tuberculosis in humans, offers variable protection in cattle. However, BCG is a highly safe vaccine, and any alternative vaccine must not only offer greater protection than BCG but also match and improve its safety profile. Mice are the most widely used animal models in tuberculosis research, particularly for pre-clinical vaccine evaluation. In these animal models, the key indicator of infection or vaccine efficacy is the mycobacteria load in the lungs. In this study, we evaluated the long-term protection conferred by vaccinating BALB/c mice with a Mycobacterium bovis triple mutant lacking the virulence genes phoP, esxA, and esxB. Our findings showed that the triple mutant protected the lungs of mice against M. bovis challenge for up to one-year post-vaccination. However, the bacterial load in the spleens predominantly comprised the vaccine strain, and the lungs also contained some of these bacteria. These results suggest that the vaccine strain persisted in the mouse organs for at least one year, which raised concerns about its potential safety for animal vaccination.